An Unusual Cause of Paediatric Epilepsy in Europe: a Case of Neurocysticercosis - Segers, Simon; Etobou, Charles; Delmelle, Françoise; Nassogne, Marie-Cécile; Bottieau, Emmanuel; Amini, Nadia; Van der Linden, Dimitri (Belgian Journal of Paediatrics, 2024)
We describe a case of symptomatic epilepsy in an 8-year-old child of Burundian origin who was admitted to an emergency department in Belgium. Neurocysticercosis is a rare cause of epilepsy outside areas endemic for Taenia solium. The 'pig tapeworm' is responsible for neurocysticercosis by larval invasion of the central nervous system. The clinical presentation and therapeutic options are reviewed, with a focus on the severity, stage, and location of the infection.